Deep Learning dalam Pendidikan Bahasa Indonesia di Perguruan Tinggi: Tinjauan Literatur dan Implikasi Praktis - Yuliani, Prima Dwi; Rahman, Fauzi; Bajuri, Muhammad Zahrul Jihadurrohim (Universitas Muhammadiyah Magelang, 2026)
Indonesian language education in higher education institutions in Indonesia faces a major challenge due to the low literacy skills of students. One solution that can be applied is to use deep learning to improve language skills. This study aims to explore the application of deep learning in Indonesian language learning with a focus on historical language analysis, spelling checking (EYD), word choice (diction), paragraph composition, and scientific writing. The method used is Systematic Literature Review (SLR) to identify and synthesize previous studies related to the application of deep learning in the context of learning. The results show that the application of deep learning can be a practical solution in efforts to improve students' understanding of Indonesian language rules through automatic feedback that helps improve spelling, sentence structure, and word choice. This approach accelerates the learning process, improves writing quality, and supports the development of students' scientific writing skills. Deep learning provides a more interactive and applicable approach to learning Indonesian in higher education.